Nasal Polyposis Showing Aggressive Behaviour – Inflammatory or Inverted Papilloma? - Kamarudin, Intan Kartika; Mohamad Fuzi, Noor Shahira (International Journal of Human and Health Sciences (IJHHS), 2024)
Nasal polyposis affects 0.2-1% of the general population. Inflammatory nasal polyp rarely behaves aggressively causing expansion to the surrounding structures without evidence of invasion. We report a case of an aggressive nasal polyp which was mistaken for inverted papilloma. A 48-year-old gentleman with underlying ischemic heart disease on aspirin presented with one month history of progressive left nasal block. He started to have frequent sneezing triggered by exposure to cold and dust. He had unilateral left straw-coloured rhinorrhea which was copious, and he was treated with oral antibiotics by the emergency department. He then developed recurrent left epistaxis which stopped after Trotter’s method. Nasal endoscopy revealed left grade three nasal polyp arising from the osteometal complex (OMC) with greenish discharge and ulcerated area. Initial biopsy showed inflammatory polyps.Computed tomography showed an expansion filling left maxillary sinus extending to nasal cavity, with no medial wall and thinning of the other maxillary walls. The lesion expands to left OMC, left sphenoethmoidal and the frontoethmoidal recess, obliterating the superior and inferior turbinates with hyperdensity in the maxillary sinus. He underwent functional endoscopic sinus surgery with left medial maxillectomy. Intraoperatively there were polypoidal mass grade 4 with epicentre in the left maxillary sinus causing erosion of the medial wall, extended around the nasolacrimal duct, the anterior and posterior ethmoids, the frontal recess, and sinus. There were dehiscence of the lamina papyracea and bone covering the anterior ethmoidal artery. The left superior and middle turbinate were unidentifiable. The histopathology findings of multiple pieces from the areas of operation were all reported as inflammatory polyps. His postoperative healing was uneventful with no nasal symptoms. In conclusion, nasal polyp with aggressive tendencies must be promptly managed surgically with close monitoring postoperatively to not miss any sinister pathology. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S56